A review of children admitted to a regional hospital in Cape Town with community acquired pneumonia - Meyer, Mandy-Lyn (Department of Paediatrics and Child Health, 2016)
Background: Pneumonia is a leading cause of death in children under - five. Epidemiology in our province at regional level has not been described since 2004, when HAART was rolled out and pneumococcal conjugate vaccination (PCV) was introduced. Objectives: Describe the demographic profile, disease severity, risks for transfer and mortality and the management of children >2 months, admitted with CAP over a one year period. Methods: Retrospective descriptive study of every second patient (>2 months to 13 years) admitted to Somerset Hospital in 2012 with the diagnosis of CAP. Demographic, clinical and outcome data were extracted from hospital records and analysed using STATA®. Results: Of 380 cases reviewed, 90% had severe disease; the median age was 9.4 months (IQR 4.8 - 23). Of these 89 (23%) were LBW (<2500g) and 75 (20%) were born premature. Median age at presentation for these groups was 5.7 months compared with 10.6 months in t erm children ( p=0.0003 ). Forty - one (12%) were severely malnourished; 34 (9%) were HIV - positive. Children below 1 0 /12 were more likely to have incomplete immunisations (57/190, p=0.011). Only 15% of TB - exposed children < 5 years were on Isoniazid Prevention Therapy (IPT). Prevalence of comorbid conditions was high. Median duration of stay was 3 days (IQR 2 - 6); this increased to 6.5 (IQR 4.5 - 9.5) with neurological disease and 6 (IQR4 - 10) with proven RSV. Seventeen patients (4.5%) required transfer to tertiary level. Mortality rate was 0.5%. Conclusion: Preventative measures must focus on populations at risk - LBW and preterm children in first year of life, malnourished children and those with comorbidities like HIV. Immunisation and IPT rates can be improved.